2000
DOI: 10.1523/jneurosci.20-02-00579.2000
|View full text |Cite
|
Sign up to set email alerts
|

Kv4.2 mRNA Abundance and A-Type K+Current Amplitude Are Linearly Related in Basal Ganglia and Basal Forebrain Neurons

Abstract: A-type K(+) currents are key determinants of repetitive activity and synaptic integration. Although several gene families have been shown to code for A-type channel subunits, recent studies have suggested that Kv4 family channels are the principal contributors to A-type channels in the somatodendritic membrane of mammalian brain neurons. If this hypothesis is correct, there should be a strong correlation between Kv4 family mRNA and A-type channel protein or aggregate channel currents. To test this hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
132
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 57 publications
8
132
0
Order By: Relevance
“…Rat DRG neurons express a diverse population of K + channel types, exhibiting as many as 6 subtypes of currents distinguishable both by voltage dependence and pharmacology (Gold et al, 1996). Three of these currents, exhibit rapid to slow rates of activation (Fedulova et al, 1998) and inactivation (Fedulova et al, 1998,Everill et al, 1998) and correspond to Kv4 subtypes (Pongs, 1992;Tkatch et al, 2000), Kv1.2 and Kv1.4 types of K + channels (Ishikawa et al, 1999). The remaining currents are non-inactivating, delayed rectifier type (Gold et al, 1996;Ishikawa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Rat DRG neurons express a diverse population of K + channel types, exhibiting as many as 6 subtypes of currents distinguishable both by voltage dependence and pharmacology (Gold et al, 1996). Three of these currents, exhibit rapid to slow rates of activation (Fedulova et al, 1998) and inactivation (Fedulova et al, 1998,Everill et al, 1998) and correspond to Kv4 subtypes (Pongs, 1992;Tkatch et al, 2000), Kv1.2 and Kv1.4 types of K + channels (Ishikawa et al, 1999). The remaining currents are non-inactivating, delayed rectifier type (Gold et al, 1996;Ishikawa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactivity for Kv4.3 and KChIP1 ( C) is concentrated in what appear to be medium-sized striatal interneurons, whereas immunoreactivity for KChIP4 can be observed in very large, multipolar interneurons. (Song et al, 1998;Tkatch et al, 2000;Liss et al, 2001;Lien et al, 2002), does not hold for all cell types, in that hippocampal dentate granule and CA3 pyramidal cells and cerebellar granule cells express high levels of colocalized Kv4.2 and Kv4.3. Coimmunoprecipitation analysis in detergent-solubilized hippocampal membranes revealed that all four KChIPs coassociate with Kv4 ␣ subunits in hippocampal membranes, confirming that the KChIPs are tightly associated with Kv4 ␣ subunits in native brain A-type channel complexes.…”
Section: Coimmunoprecipitation Analysesmentioning
confidence: 97%
“…However, several studies reported a straight relation between A-type K+ currents and Kv4 channels in neostriatal neurons (Tkatch et al 2000). Kv4 channels in the spiny neurons of the striatal medium regulate b-AP (Day et al 2008) and participate in clustering and firing bursting patterns (Falk et al 2006).…”
Section: Spatial Learning Is Related To Transient Kv4 Up-regulationmentioning
confidence: 99%